Correction to: Transient Sub-cellular Localization and In Vivo Protein-Protein Interaction Study of Multiple Abiotic Stress Responsive AteIF4A-III and AtALY4 Proteins in Arabidopsis thaliana - Baruah, Indrani; Baruah, Geetanjali; Sahu, Jagajjit; Singha, Dhanawantari L.; Dekaboruah, Hariprasanna; Velmurugan, Natarajan; Chikkaputtaiah, Channakeshavaiah (Plant molecular biology reporter, 2021)
The affiliation 2 in the published article was Academy of Scientific and Innovative Research (AcSIR), CSIR-NEIST Campus, Jorhat, Assam 785,006, India.